THE USE OF TWO STAY TWO STRAY IN IMPROVING STUDENTS’ READING COMPREHENSION - Ema Dauyah; Intania Purnama (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
This study was aimed to investigate whether Two Stay Two Stray technique can improve students’reading comprehension. It also aimed to find out the students response toward Two Stay Two Stray technique. This research used an experimental study. Based on the research findings, the researcher found that teaching reading comprehension by using Two Stay Two Stray technique was better in experimental group than control group. It was shown from the result that score mean score of pre-test of experimental group was sligtly better than the control group (38,5 and 39,13). Whereas the mean score of post-test of the experimental group also revealed the same result where the mean score of experimental group wa higher than the control group (79,13 and 68,83). and the mean score of post-test of experimental group was 79,13. Then, t-score pre-test of both techniques was 0,21 and t-score of post-test of both techniques was 3,04. So, t-score post-test is higher than t-score of pre-test. From the questionnaire was positive responses.